Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 1 - Introduction to Algebraic Expressions - 1.2 The Commutative, Associative, and Distributive Laws - 1.2 Exercise Set - Page 18: 101



Work Step by Step

Solve for x=0. $3(2+x)=3(2+0)=3(2)=6$ $6+x=6+0=6$ Solve for x=1. $3(2+x)=3(2+1)=3(3)=9$ $6+x=6+1=7$ Just because two expressions have the same result for one input does not guarantee they will give the same result for all inputs. To be equivalent the expressions must have the same result for any input value.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.